Location and distribution of fire stations. Case Study : Wilayah Persekutuan / Juliah Jani dan Norsiah Din - Jani, Juliah; Din, Norsiah (Faculty of Architecture, Planning and Surveying, 1983)
The loss of property through fires is increasing since the country's independence in 1957 with tall buildings mushrooming all over the city and the increase in traffic volumes has brought about problems to the Fire Department. Earlier, the planning of fire stations is based only on the criteria of time taken to travel to the affected areas, not taking into consideration the landuses and population of the areas, Today, the fire department encounter a lot of problems in providing efficient services to the public. Chapter one discusses the meaning of fire, the importance of fire stations and its relation with planning process. This chapter will also include the literature review of fire stations. It will outline the importance of fire stations and the factors affecting the location and distribution of fire stations, Chapter two outline the history of fire stations in Wilayah Persekutuan, their criteria used in the establishment of fire stations, the objectives and functions of fire stations the organizational structure and hierarchy of fire stations in Wilayah Persekutuan.